Digital Transformation in Hospital Management: Building Readiness for Society 5. - I Gede Eka Handrean; Ivanda Rian Pratama; Dita Rahma Sumarna; Ricky Fakhrazi; Saperyanus Rejauw; Vip Paramarta (CV. Inara, 2025)
This study examines digital transformation strategies in hospital management and assesses organizational readiness for Society 5.0 implementation through a systematic literature review. The research employed a comprehensive narrative review methodology, analyzing peer-reviewed publications from 2014 to 2024 across major scientific databases including PubMed, Scopus, Google Scholar, and Science Direct. Our analysis identified four critical factors for successful digital transformation in healthcare settings: (1) robust technological infrastructure integrated with competent human resources and adaptive organizational culture; (2) transformative leadership and sustained management commitment; (3) systematic monitoring and continuous evaluation frameworks; and (4) enhanced patient engagement mechanisms that leverage digital technologies to improve healthcare service quality. These findings provide practical insights for healthcare institutions navigating digital transformation while preparing for Society 5.0 challenges. The study contributes to the growing body of knowledge on healthcare digitalization by offering an integrated framework for assessing and implementing digital transformation initiatives in hospital settings.